Angiogenesis and lymphangiogenesis as prognostic factors after therapy in patients with cervical cancer - Biedka, Marta; Makarewicz, Roman; Kopczyńska, Ewa; Marszałek, Andrzej; Goralewska, Alina; Kardymowicz, Hanna (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: This retrospective study attempts to evaluate the influence of serum vascular endothelial growth factor C (VEGF-C), microvessel density (MVD) and lymphatic vessel density (LMVD) on the result of tumour treatment in women with cervical cancer. Material and methods : The research was carried out in a group of 58 patients scheduled for brachytherapy for cervical cancer. All women were patients of the Department and University Hospital of Oncology and Brachytherapy, Collegium Medicum in Bydgoszcz of Nicolaus Copernicus University in Toruń. VEGF-C was determined by means of a quantitative sandwich enzyme immunoassay using a human antibody VEGF-C ELISA produced by Bender MedSystem, enzyme-linked immunosorbent detecting the activity of human VEGF-C in body fluids. The measure for the intensity of angiogenesis and lymphangiogenesis in immunohistochemical reactions is the number of blood vessels within the tumour. Statistical analysis was done using Statistica 6.0 software (StatSoft, Inc. 2001). The Cox proportional hazards model was used for univariate and multivariate analyses. Univariate analysis of overall survival was performed as outlined by Kaplan and Meier. In all statistical analyses p < 0.05 (marked red) was taken as significant. Results : In 51 patients who showed up for follow-up examination, the influence of the factors of angiogenesis, lymphangiogenesis, patients’ age and the level of haemoglobin at the end of treatment were assessed. Selected variables, such as patients’ age, lymph vessel density (LMVD), microvessel density (MVD) and the level of haemoglobin (Hb) before treatment were analysed by means of Cox logical regression as potential prognostic factors for lymph node invasion. The observed differences were statistically significant for haemoglobin level before treatment and the platelet number after treatment. The study revealed the following prognostic factors: lymph node status, FIGO stage, and kind of treatment. No statistically significant influence of angiogenic and lymphangiogenic factors on the prognosis was found. Conclusion : Angiogenic and lymphangiogenic factors have no value in predicting response to radiotherapy in cervical cancer patients.